ANALISIS PERAN KADER DALAM PROGRAM SAN-PIISAN DI KOTA SEMARANG - Purnomo, Alisya Ihsani; Hanani, Retna; Rahman, Amni Zarkasyi (Journal of Public Policy and Management Review, 2024)
The high maternal mortality rate (MMR) cases in Semarang City in 2015, totaling 35 cases of MMR, has become a health issue that requires an appropriate health solution. Therefore, the Semarang City government established the SAN-PIISAN Program, which focuses on addressing MMR, child mortality (AKB), and stunting. The SAN-PIISAN Program is a health program that involves collaboration between the government, private sector, and civil society. In implementing the program, there is involvement of cadre roles as part of the civil society. However, there are issues with the cadre roles, the lack of awareness among cadres to fulfill their roles and the shortage of cadre workforce, resulting in dual roles. The aim of this research is to understand the role of cadres in the SAN-PIISAN Program in Semarang City and to identify the supporting and hindering factors for cadres in fulfilling their roles. The research method used is descriptive qualitative. The data collection techniques include observation, interviews, documentation, and literature review. The theory used is the role theory according to Jim Ife and Frank Tesoriero, which includes facilitative, educational, representative, and technical roles. The result of the research indicate that cadres have been fulfilling their roles, but they have some lack initiative in technical roles such as data collection and reporting. The supporting factor for cadre roles in fulfilling their duties is role behavior or a responsibility they had, while the hindering factors include the occurrence of dual roles among cadres and excessive job demands